Pharmacognostical and Antifungal Activity of Selected Seaweeds from Gulf of Mannar Region - Sekaran Sridhar1*,Jebamalai Suresh Kumar1 and Sarangam Babu2, Pandurangan Aruna1, Periasamy Mansuya1 (Recent Research in Science and Technology, 2010)
Abstract The antifungal activities of six important seaweeds namely the green seaweed Cladophora glomerata, Ulva lactuca and Ulva reticulata, the red seaweed Gracilaria corticata and Kappaphycus alvarezii and the brown seaweed Sargassum wightii were screened against fungal pathogens Aspergillus niger, Aspergillus flavus, Aspergillus fumigatous, Saccharomyces cervisiae and Mucor indicus. The zone of inhibition ranged between 56 - 8mm in aqueous extract and 56 – 4mm in methanolic extract. The maximum activity (56mm) was recorded from 200mg of aqueous extract of Ulva lactuca against Aspergillus flavus and minimum (8mm) by Gracilaria corticata against Mucor indicus at 50 mg level whereas, the methanolic extract showed the maximum activity (56mm) was recorded from 200mg of U. lactuca against Aspergillus niger and minimum (4mm) by 50 mg of Ulva reticulata against Aspergillus flavus. Keywords: Seaweeds, Antifungal activity, Methanolic extract, Aqueous extract, Pharmacognosy